X-ray diffractometric study of HDPE/GaAs and HDPE/GaAs<Te> composites - Gadzhieva, N.N.; Ahmadova, G.B.; Melikova, S.Z.; Asadov, F.G. (Physics and Chemistry of Solid State, 2023)
High-density polyethylene sheets (HDPE), HDPE/GaAs and HDPE/ GaAs<Te> composites with GaAs and GaAs<Te> semiconductor fillers were studied by X-ray diffractometry at room temperature. The degree of crystallization of these samples was calculated and it was determined that the inclusion of fillers in the polymer matrix (x=1-10% composite) leads to an increase in the degree of crystallization by 1.3-1.4 times. The obtained results are explained by the change of the upper molecular structure of the polymer.